Takeout 25 : a community-driven entrepreneurial initiative in Oak Park, Illinois - Mulloth, Bala; Watt, Ariel (London : SAGE Publications: SAGE Business Cases Originals, 2023)
In this case, we study the growth, evolution, and innovation of Takeout 25, a socially minded initiative that helped revitalize Oak Park's restaurant industry and local economy in the midst of the COVID-19 pandemic. The brainchild of Ravi Parakkat, an Oak Park citizen and village trustee, Takeout 25's mission was to orchestrate a movement championing the need for financially viable, community-oriented solutions to keep residents safe while allowing restaurants to prosper. By engaging closely with the local community and building partnerships with a range of restaurants and small businesses, Takeout 25 has set itself apart as a viable model for Oak Park and other cities nationally to adopt to counter the economic fallout of the pandemic. In addition to investigating the Takeout 25 team's social motivations and shared values that contributed to the initiative's goals and vision, students will discuss the various strategic decisions and dilemmas the team faces as they seek to maximize impact in the years ahead.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies; Community leadership -- Illinois -- Case studies